Hepatocyte-specific IKKβ expression aggravates atherosclerosis development in APOE*3-Leiden mice - Wong, Man C. (2011)
OBJECTIVE: The liver is the key organ involved in systemic inflammation, but the relation between hepatic inflammation and atherogenesis is poorly understood. Since nuclear factor-κB (NF-κB) is a central regulator of inflammatory processes, we hypothesized that chronically enhanced hepatic NF-κB activation, through hepatocyte-specific expression of IκB kinase-β (IKKβ) (LIKK), will aggravate atherosclerosis development in APOE*3-Leiden (E3L) mice. METHODS AND RESULTS: E3L.LIKK and E3L control littermates were fed a Western-type diet for 24 weeks. E3L.LIKK mice showed a 2.3-fold increased atherosclerotic lesion area and more advanced atherosclerosis in the aortic root with less segments without atherosclerotic lesions (11 vs. 42%), and more segments with mild (63% vs. 44%) and severe (26% vs. 14 %) lesions. Expression of LIKK did not affect basal levels of inflammatory parameters, but plasma cytokine levels tended to be higher in E3L.LIKK mice after lipopolysaccharide (LPS) administration. E3L.LIKK mice showed transiently increased plasma cholesterol levels, confined to (V)LDL. This transient character resulted in a mild (+17%) increased cumulative plasma cholesterol exposure. CONCLUSION: We conclude that selective activation of NF-κB in hepatocytes considerably promotes atherosclerosis development which is (at least partly) explained by an increased sensitivity to proinflammatory triggers and transiently increased plasma cholesterol levels.